Soil erosion in relation to farm productivity, expecditure and food and nutritional intake of children of irrigated rice farmers in General Santos City - Hairol, Sitti Kulsum D. (School of Management, University of the Philippines Mindanao, 2016)
Soil erosion is one of the major problems faced in agriculture globally in recent times. With the role of the irrigated farmers in the supply of rice in the Philippines and the unsparing effects of soil erosion to rice farming, there is a need to measure the effect of soil erosion to the productivity as well as expenditure, food and nutritional intake of children of these farmers in order to promote policies as they play a vital role in the supply of rice in the country. The study compared the productivity, expenditure and food and nutritional intake of children of the irrigated rice farmers of General Santos City with no and slight erosion levels. Geographic Information System (GIS) was used in identifying the erosion level of the areas. Results showed that the presence of slight erosion in the area has no significant effect on the productivity with respect to the area with no erosion. Further, results for the comparison of yield, income expenditure and consumption and food and nutritional intake of children also showed no significant difference. Thus the presence of slight erosion is not a threat to rice production and expenditure and consumption of farmers since slightly eroded areas are still sustainable for local farming practices. Further, more serious problems such as drought which is also a manifestation of climate change and rat infestation is a more serious problem than soil erosion in slightly eroded rice farms.